Polymeric Nanoparticles, Nanospheres and Nanocapsules, for Cutaneous Applications - Sílvia S. Guterres; Marta P. Alves; Adriana R. Pohlmann (AboutScience Srl, 2007)
This review presents an overview about pharmaceutical and cosmetic topical products containing polymeric nanoparticles (nanospheres and nanocapsules), reporting the main preparation and characterization methods and the studies of penetration and transport of substances through the skin. The penetration and transport extent of those systems through the skin depends on the ingredients chemical composition, on the encapsulation mechanism influencing the drug release, on the size of nanoparticles and on the viscosity of the formulations. The polymeric nanoparticles are able to modify the activity of drugs, delay and control the drug release, and increase the drug adhesivity or its time of permanence in the skin. Briefly, the nanoparticles can be useful as reservoirs of lipophilic drugs to deliver them in the stratum corneum becoming an important strategy to control their permeation into the skin.